2006
DOI: 10.1093/annonc/mdl302
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancy risk associated with treatment of Hodgkin's lymphoma: meta-analysis of the randomised trials

Abstract: Administration of CT in addition to RT as initial therapy for HL decreases overall SMR by reducing relapse and need for salvage therapy. Administration of RT additional to CT marginally increases overall SMR in advanced stages. Breast cancer risk (but not SMR in general) was substantially higher after EF-RT. Caution is needed in applying these findings to current therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(90 citation statements)
references
References 71 publications
6
79
0
5
Order By: Relevance
“…In a recent report, a switch from a 35-Gy mantle field to involved field radiotherapy (IFRT) at the same total dose reduced the estimated 20-year excess RR of BC by 63% (Hodgson et al, 2007). This model is consistent with meta-analysis data of clinical trials demonstrating an odds ratio of 3.25 (P ¼ 0.04) for the development of BC for women treated with extended field vs IFRT (Franklin et al, 2006). It may be possible to avoid radiotherapy altogether in a proportion of patients with both early and advanced stage HL, thus reducing the detrimental long-term sequelae of treatment for these individuals.…”
Section: Discussionsupporting
confidence: 70%
“…In a recent report, a switch from a 35-Gy mantle field to involved field radiotherapy (IFRT) at the same total dose reduced the estimated 20-year excess RR of BC by 63% (Hodgson et al, 2007). This model is consistent with meta-analysis data of clinical trials demonstrating an odds ratio of 3.25 (P ¼ 0.04) for the development of BC for women treated with extended field vs IFRT (Franklin et al, 2006). It may be possible to avoid radiotherapy altogether in a proportion of patients with both early and advanced stage HL, thus reducing the detrimental long-term sequelae of treatment for these individuals.…”
Section: Discussionsupporting
confidence: 70%
“…13 For patients treated at age 25 years with a chest radiation dose of at least 40 Gy without alkylating agents, the estimated cumulative absolute risks of breast cancer by age 35, 45, and 55 years were 1.4%, 11.1%, and 29.0%, respectively. Several studies have demonstrated a direct correlation between breast cancer risk and radiation field size [14][15][16][17] and also showed that smaller fields and treatment volume are associated with a significantly lower risk of breast cancer. In a population-based study comparing outcome of de novo breast cancer versus breast cancer after HL, women with localized breast cancer after HL had a significantly increased 2-fold risk of death from breast cancer compared with patients with de novo breast cancer.…”
Section: Second Malignancymentioning
confidence: 99%
“…The risk of developing secondary cancers is highest when RT is used as a component of first-line treatment. A meta-analysis by Franklin et al 89 showed that the risk of developing secondary cancers was lower with combined modality treatment than with RT alone as the initial treatment. The risk was marginally higher with combined modality treatment compared with chemotherapy alone as initial treatment.…”
Section: Monitoring For Late Effectsmentioning
confidence: 99%